Monopedia: Staying single is good enough - the hyper way for web scale applications - Schüle, Maximilian E.; Schliski, Pascal M.N.; Hutzelmann, Thomas; Rosenberger, Tobias; Leis, Viktor; Vorona, Dimitri; Kemper, Alfons; Neumann, Thomas (Proceedings of the VLDB Endowment, 2017)
In order to handle the database load for web scale applications, the conventional wisdom is that a cluster of database servers and a caching layer are essential. In this work, we argue that modern main memory database systems are often fast enough to consolidate this complex architecture into a single server (plus an additional fail over system). To demonstrate this claim, we design the Monopedia Benchmark, a benchmark for web scale applications modeled after Wikipedia. Using this benchmark, we show that it is indeed possible to run the database workload of one of the largest web sites in the world on a single database server.
CRIS-Team Scopus Importer:2021-04-12